Kualitas Karkas (Berat Karkas, Persentase Karkas Dan Lemak Abdomen) Ayam Broiler yang Diberi Kombinasi CPO (Crude Palm Oil) dan Vitamin C (Ascorbic Acid) dalam Ransum sebagai Anti Stress - K Subekti; H Abbas; K. A. Zura (Universitas Andalas, 2012)
The research was conducted to determine the effect of CPO (Crude Palm Oil) and Vitamin C (ascorbic acid) combination in the diet as an anti stress on broilers carcass and abdominal fat of broilers. The research was carried out in the poultry housing at UPT of Animal Science Faculty, Andalas University Padang for 42 days and 100 unsex broiler were used. The method of this research was an experiment with completely randomized design with 5 treatments and 4 replications. Replicates each consisting of 5 broilers were placed in a cage with a group size of 75 x 60 x 60cm. Results of analysis of variance showed that the combination treatment CPO and Vitamin C significantly (P<0.05) on carcass weight, but the percentage of carcass, and percentage of abdominal fat treatment have different effects and not significant (P>0.05). In this research the best trends CPO 3% and Vitamin C 500 ppm in the ration.